A novel totally biodegradable device for effective atrial septal defect closure: A 2‐year study in sheep. (5th August 2018) - Lu, Wenxin; Ouyang, Wenbin; Wang, Shouzheng; Liu, Yao; Zhang, Fengwen; Wang, Weiwei; Pan, Xiangbin
Abstract : Objective: To evaluate the feasibility, efficacy, and safety of a fully biodegradable poly lactic acid (PLA)‐based occluder for atrial septal defect (ASD) closure in an animal model. Methods: ASDs, approximately 12‐mm in diameter, were generated in sheep ( n  = 18) by needle puncture and balloon dilatation. For ASD closure, occluders were implanted by percutaneous transcatheter approach under echocardiographic guidance. Outcomes were evaluated by transthoracic echocardiography, electrocardiography, blood testing, and histology within the follow‐up period ranging from 1 month to 2 years. Results: All occluders were successfully implanted. During follow‐up, no animal died; rectal temperatures, blood test results, and electrocardiograms were within normal ranges; and transthoracic echocardiograms, macroscopic studies, and histopathological and electron microscopic examination demonstrated that the occluders were well positioned, with no shifting, residual shunts, severe inflammation, thrombus formation, atrioventricular valve insufficiency, cardiac erosion or arrhythmias. The occluders gradually embedded into the endocardial tissue of the hosts with complete endothelialization and disk absorption at 12 months, and a distinct molecular weight decrease of the framework (to 9% of initial) at 24 months after implantation. Conclusions: In a sheep model, the use of totally biodegradable occluders appears feasible, efficacious and safe for ASD closure. Studies in humans are ongoing.